“Dickens as a Tool for TESOL in Uzbekistan: Literature in Language Learning” (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
English consists of four essential skills: reading, speaking, listening, and writing. However, this paper specifically focuses on reading skills. Additionally, there are various methods and approaches to teaching reading, including theoretical perspectives on reading comprehension and an analysis of effective strategies for improving it. One particularly effective method inreading comprehension will also be reviewed can inspire students to develop a genuine interest in reading. The true essence of teaching lies in helping students deeply understand the material, rather than simply presenting information and assuming they will grasp it. The goal is to create a lasting impact that motivates students to continue reading on their own. According to researchers, another effective way to enhance students' comprehension is through text structure tasks. Engaging students in oral activities related to text structure helps them process and integrate information more effectively. For example, asking students questions about the text's structure can